2008
DOI: 10.1577/m06-291.1
|View full text |Cite
|
Sign up to set email alerts
|

Escaping the Surface: The Effect of Capture Depth on Submergence Success of Surface‐Released Pacific Rockfish

Abstract: We evaluated the effect of capture depth and fish size on the ability of several Pacific rockfishes Sebastes spp. to resubmerge after hook‐and‐line capture and surface release. We observed fish as they were released into a bottomless floating enclosure, and we recorded submergence success within a 5‐min time limit. Submergence success was greater than 80% for all rockfish captured in depths less than 30 m. Yellowtail rockfish S. flavidus (N = 51) were 100% successful at submerging in less than 49 s at all dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 7 publications
6
64
1
Order By: Relevance
“…For example, depth may be most important for taxa possessing a physoclistous (closed) swim bladder, such as white hake and cod in this study (e.g., St. John and Syers, 2005;Parker et al, 2006;Hannah et al, 2008). However, the effect of depth may not manifest itself only as barotrauma for fish, but also as an effect of thermal shock resulting from depth-dependent temperature gradients, such as those generally found in the southern Gulf of St. Lawrence (Koutitonsky and Bugden, 1991) for the locations and dates at which most fishing took place in 2005-2006. Failure to infer an effect of depth on vitality for other taxa in our study may also have reflected a lack of contrast in the depths over which they were captured during the study (Table 3).…”
Section: Success Of Live Releasementioning
confidence: 94%
“…For example, depth may be most important for taxa possessing a physoclistous (closed) swim bladder, such as white hake and cod in this study (e.g., St. John and Syers, 2005;Parker et al, 2006;Hannah et al, 2008). However, the effect of depth may not manifest itself only as barotrauma for fish, but also as an effect of thermal shock resulting from depth-dependent temperature gradients, such as those generally found in the southern Gulf of St. Lawrence (Koutitonsky and Bugden, 1991) for the locations and dates at which most fishing took place in 2005-2006. Failure to infer an effect of depth on vitality for other taxa in our study may also have reflected a lack of contrast in the depths over which they were captured during the study (Table 3).…”
Section: Success Of Live Releasementioning
confidence: 94%
“…The severity of barotrauma symptoms increases with capture depth (Al os 2008; Hannah et al 2008a;Brown et al 2010;Campbell et al 2010b;Butcher et al 2012), and the majority of deepwater catch-and-release studies have identified this variable as the greatest predictor of release mortality. Fish classified as fate "unknown" from acceleration and depth profiles are omitted in the analysis; therefore, the sample size (n) for each group is equal to the number of fish tagged minus the unknowns.…”
Section: Red Snapper Delayed Mortalitymentioning
confidence: 99%
“…Increasing depth of capture has also been shown to be negatively related to submergence ability of three species of rock fish (Sebastes spp.) (Hannah et al, 2008). Recaptured fish showed significantly lower impairment than non-recaptured fish as measured by BtR.…”
Section: Btr Impairment and Mortalitymentioning
confidence: 90%